Stigma Sosial Pejabat pada Kolom Komentar Akun X @Notaslimboy Tinjauan Pragmatik Erving Goffman - Salzabila, Nafa Syahwa; Suriadi, Suriadi (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2025)
This study aims to reveal the dynamics of social stigma formation towards public officials on social media by reviewing the comments on @notaslimboy's X account, specifically in the case of the debate between Dedi Mulyadi and Aura Cinta. Using a pragmatic approach and Erving Goffman's stigma theory, this study analyzes how netizen comments shape the virtual identity of public figures through negative labeling categorized into three types of stigma: blemishes of individual character, tribal stigma, and abominations of the body. Data was purposively obtained based on high interaction and strong labeling content. The results showed that the majority of stigmas that emerged were related to moral character defects, followed by political group-based stigmas. Social media proved to be a fertile arena for stigma reproduction as it allowed for the rapid and widespread formation of collective opinions, which then influenced public perceptions of the credibility and identity of officials. In addition, interactions in the comments section also show a process of resistance and identity negotiation. This research confirms that social media is not only a communication tool, but also a symbolic space where social identities are negotiated and power is redefined by a digital society.